Capability and Attitude Towards Research of Teachers: Basis for Research Capacity Building Program - Satsatin, King Arnold (Edukhasi: Jurnal Inovasi Pendidikan, 2025)
This quantitative study investigated the research capability and attitude towards research among public school teachers in cluster 10 of Schools Division of Sta. Rosa City, Laguna, Philippines, aiming to develop a data-driven research capacity building program. Specifically, it examined the significant differences in teachers’ research capabilities and attitudes when grouped according to demographic profiles—such as age, sex, teaching position, length of service, and highest educational attainment. Furthermore, it explored the relationship between teachers’ research capabilities and their attitudes towards research in terms of research usefulness, anxiety, positive disposition, relevance in life, and perceived difficulty. The study utilized a descriptive-correlational design and employed validated survey instruments to gather data from teacher-respondents. Findings revealed that significant differences in research capability exist when grouped according to age, sex, and teaching position, particularly in the areas of methodology, results and discussion, and conclusion writing. Similarly, attitude towards research varied significantly across sex, teaching position, and length of service, especially regarding research usefulness, positive attitude, and relevance in life. Correlation analysis using Spearman’s rho indicated moderate to low positive correlations between teachers’ research capabilities and their attitudes towards research usefulness and relevance in life. However, negligible and non-significant relationships were observed in terms of research anxiety and perceived difficulty. These findings suggest that while many teachers possess basic research knowledge, their attitudes and confidence levels remain inconsistent across demographic variables. The results of this study underscore the need for differentiated and targeted research capacity building interventions. Programs must focus not only on enhancing technical skills but also on fostering positive attitudes and reducing research anxiety among teachers. A research capability training program is hereby proposed as the output of the study.